2021
DOI: 10.1371/journal.pone.0245782
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal vegetable intake during pregnancy and allergy in offspring: Japan Environment and Children’s Study

Abstract: The association between maternal diet during pregnancy and allergy in offspring remains contentious. Here, we examined the association between maternal intake of vegetables and related nutrients during pregnancy and allergic diseases in offspring at one year of age. A cohort of 80,270 pregnant women enrolled in the Japan Environment and Children’s Study were asked to respond to a food frequency questionnaire during pregnancy and the International Study of Asthma and Allergies in Childhood questionnaire at one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…An unexpected finding was the link of vegetable intake with FPIAP. Other studies associated maternal vegetable intake with allergy prevention ( 25 , 32 ), although offspring of women with a higher intake of total vegetables, folate-rich, and green and yellow vegetables were reported to have a higher risk of allergies, including FA ( 33 ). In countries where the MedDiet is widespread, vegetables are frequently incriminated in FA ( 34 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected finding was the link of vegetable intake with FPIAP. Other studies associated maternal vegetable intake with allergy prevention ( 25 , 32 ), although offspring of women with a higher intake of total vegetables, folate-rich, and green and yellow vegetables were reported to have a higher risk of allergies, including FA ( 33 ). In countries where the MedDiet is widespread, vegetables are frequently incriminated in FA ( 34 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that children of mothers who consumed less than 1.5 servings of leafy vegetables per day had a higher risk of wheezing compared to children of mothers who consumed more than 1.5 servings per day. This association was independent of other factors such as maternal smoking during pregnancy, family history of asthma, and birth weight 38 . Vegetables and fruits are rich in antioxidants and other anti-inflammatory compounds that may help to reduce the risk of allergic disease in offspring.…”
Section: Discussionmentioning
confidence: 71%
“…Yuzaburo Inoue 1,2 Yu Yamamoto 3 Shigenori Suzuki 3 Shingo Ochiai 1,4 Akifumi Eguchi 5 Taiji Nakano 1 Fumiya Yamaide 1,6 Satomi Hasegawa 1 Hiroyuki Kojima 7 Chisato Mori 4,5 Yoichi Kohno 1 Hiroyuki Suganuma 3 Naoki Shimojo 1,5…”
Section: Lettersmentioning
confidence: 99%
“…However, previous studies evaluating the association between maternal vegetable intake during pregnancy and eczema in offspring have shown inconsistent results. [4][5][6] These studies did not measure the individual serum carotenoid levels of mothers or children and in breast milk; therefore, appropriate nutritional interventions in maternal and early infant intake of foods containing carotenoids to prevent AD remain unclear.…”
mentioning
confidence: 99%